1983
DOI: 10.1002/ijc.2910310207
|View full text |Cite
|
Sign up to set email alerts
|

Persistent in vitro infection by human T‐cell leukemia‐lymphoma virus (HTLV) of normal human T‐lymphocytes from blood relatives of patients with HTLV‐associated mature T‐cell neoplasms

Abstract: Human T-cell lymphoma-leukemia virus (HTLV), a novel type-C retrovirus, has been identified in tumor cells of patients with mature T-cell neoplasms. Attempts to transmit the first isolate of HTLV designated HTLV-I , , , to secondary cultures of animal cells and several attempts to transmit HTLV t o normal human T cells, activated with PHA and grown with T-cell growth factor (TCGF), obtained from randomly selected normal adult donors were unsuccessful. Peripheral blood leukocytes were obtained from blood relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 41 publications
1
16
1
Order By: Relevance
“…These cells express HTLV proteins, release type4 virus particles and contain surface receptors for TCGF. These results demonstrate that HTLV isolated from T-cell leukemic to numerous human and other mammalian cell lines by cell-free procedures, as well as to fresh human hematopoietic cells, including umbilical cord blood leukocytes, were negative, with the exception of expression of viral proteins in cultured T cells from close relatives of the leukemic patient (Ruscetti et al, 1983, and our personal observation). However, many other sources of HTLV can infect fresh cord blood leukocytes Miyoshi ef al., 1981b;Yamamoto et al, 1982) and as we detail here, new HTLV isolates from patients living in different parts of the world can infect and transform fresh umbilical cord blood lymphocytes.…”
supporting
confidence: 72%
“…These cells express HTLV proteins, release type4 virus particles and contain surface receptors for TCGF. These results demonstrate that HTLV isolated from T-cell leukemic to numerous human and other mammalian cell lines by cell-free procedures, as well as to fresh human hematopoietic cells, including umbilical cord blood leukocytes, were negative, with the exception of expression of viral proteins in cultured T cells from close relatives of the leukemic patient (Ruscetti et al, 1983, and our personal observation). However, many other sources of HTLV can infect fresh cord blood leukocytes Miyoshi ef al., 1981b;Yamamoto et al, 1982) and as we detail here, new HTLV isolates from patients living in different parts of the world can infect and transform fresh umbilical cord blood lymphocytes.…”
supporting
confidence: 72%
“…The virus could only be isolated from T-lymphocytes of leukemia patients after culture in the presence of T-cell growth factor (Poiesz et al, 1980). Similarly, co-cultivation of the virus-producing cells with cord lymphocytes, or infection with cell-free virus, led to the establishment of transformed lines bearing the characteristics of mature T but not B or other cells (Chen et ul., 1983;Hoshino et al, 1983;Ruscetti et al, 1983). However, our data and other recent studies suggest that HTLV-like viruses may have a wider host range than was previously assumed.…”
Section: Discussioncontrasting
confidence: 78%
“…Chosa et al (1982), on the other hand, reported that cell-free virus from MT-2 cell cultures infected and induced ATLA in the presence of phytohaemagglutinin in leukocytes from randomly selected healthy individuals without anti-ATLA antibody. Likewise, Ruscetti et al (1983) reported that PBL from members of the family of patient CR who had no anti-HTLV antibody, were infectible by cell-free virus, whereas PBL from unrelated subjects were not. It was shown by means of membrane immunofluorescence that cell-free ATLV derived from MT-2 cells was able to adsorb to many haematopoietie cell lines from various species, such as man, mouse and marmoset, thus suggesting the presence of virus receptors in a wide range of animal tissues (Yamamoto et al, 1984a).…”
Section: Cell-lree Viral Ir!ti'ctionmentioning
confidence: 99%